Sex-disaggregated Data in Climate, Agriculture and Food Security: An assessment of current trends and gaps - Partey, Samuel T.; North, Hanna; Huyer, Sophia (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This report reviews trends and availability of sex-disaggregated data on various aspects of gender and CSA, including agricultural innovation, decision-making, time use and access to resources. It uses data collected by the CGIAR and other organizations to analyse gender trends at global, regional and national levels.